Antiproliferative activity of leaf, fruit pericarp essential oils of Syzygium palodense - S.P. Smitha Rani; S.R. Rajani Kurup; S. Ajikumaran Nair; P. Nusaifa Beevi; Sreeja Thankappan; Sabulal Baby (Elsevier, 2021)
Background: Syzygium palodense is an unexplored species endemic to the southern Western Ghats in India. Purpose: Here we report the chemical profiles of essential oils (EOs) of the leaves and fruit pericarps of S. palodense and their antiproliferative activities against C6 glioma and Dalton's Lymphoma Ascites (DLA) cells. Methods: S. palodense leaves and fruit pericarp EOs were isolated by hydrodistillation and characterized by gas chromatographic (GC/FID, GC/MS) techniques. Antiproliferative activities of EOs were elucidated by MTT, phase contrast/fluorescent microscopic and flow cytometric assays. Results: Thirty six (99.92%) constituents were identified from S. palodense fruit pericarp EO, with (E)-β-ocimene (63.20%), myrcene (15.79%) and (Z)-β-ocimene (9.70%) as its major constituents. Sixty nine (99.40%) constituents were identified in the leaf EO, and the major ones were (E)-β-ocimene (30.58%), (E)-caryophyllene (14.23%), δ-selinene (13.89%), γ-himachalene (7.59%), myrcene (8.38%) and (Z)-β-ocimene (5.68%). Both leaf and fruit pericarp EOs showed significant cytotoxicity in C6 glioma and Dalton's Lymphoma Ascites (DLA) cells with very low CD50 values of 1.8, 1.2 µg/ml and 4.8, 1.1 µg/ml, respectively. MTT, phase contrast/fluorescent microscopic and flow cytometric assays revealed the cytotoxic mechanism of these EOs in C6 glioma and DLA cells as induction of apoptosis. Conclusion: This is the first report of the chemical profiles and biological activities of EOs of S. palodense. Both leaf and fruit pericarp EOs displayed strong antiproliferative activity (very low CD50 values) against C6 glioma and DLA cells.